Presence of an audience and consistent interindividual differences affect archerfish shooting behaviour. (July 2018) - Jones, Nick A.R.; Webster, Mike; Templeton, Christopher N.; Schuster, Stefan; Rendell, Luke
Abstract : The social environment can play an important role in shaping the foraging behaviour of animals. In this study we investigated whether archerfish, Toxotes jaculatrix, display any behavioural changes in response to the presence of an audience while using their specialized foraging tactic of shooting, spitting precisely aimed jets of water, at prey targets. As any prey items shot down are potentially available to competitors, we hypothesized that shooting fish would be sensitive to the presence of potential competitors, especially given the suggestion that, in the wild, this species shows intraspecific kleptoparasitism and faces interspecific competition. We found that in the presence of another fish, archerfish took longer to shoot, made more orientations (aiming events) per shot, and tended to be closer to the target at the time of shooting. Additionally, archerfish showed high interindividual differences in latency to shoot, and these differences were consistent across contexts, with and without an audience. Our results show that archerfish are sensitive to, and adjust their shooting behaviour in response to, the presence of an audience and highlight the importance of social context in this fish species. We also suggest that interindividual differences may play an important role in archerfish shooting behaviour. This study highlights the importance of social effects and competition on foraging behaviour and decision making. Further work in this species could explore whether differences in competitive foraging ability are linked to sensitivity to the presence of an audience. Highlights: Archerfish prey shooting behaviour is affected by the presence of conspecifics. Latency to shoot and number of aiming events increased with an audience. Archerfish show consistent interindividual differences in latency to shoot.